Prevalence of Dementia and Associated Factors among Older Adults in Latin America during the COVID-19 Pandemic - Soto Añari, M. (2021)
Background: The COVID-19 pandemic has had a great impact on cognitive health in Latin American older adults, increasing the risk of cognitive impairment and dementia. Our objective was to analyze the prevalence of dementia and the associated factors in Latin American older adults during SARS-CoV-2 pandemic. Methods: A multicentric first phase cross-sectional observational study was conducted during the SARS-CoV-2 pandemic. Five thousand two hundred and forty-five Latin American adults over 60 years of age were studied in 10 countries: Argentina, Bolivia, Chile, Colombia, Ecuador, Guatemala, Mexico, Peru, the Dominican Republic, and Venezuela. We used the telephone version of Montreal Cognitive Assessment, the ?Alzheimer Disease 8? scale for functional and cognitive changes, and the abbreviated version of the Yesavage depression scale. We also asked for sociodemographic and lockdown data. All the evaluation was made by telephone. Cross-tabulations and χ2 tests were used to determine the variability of the prevalence of impairment by sociodemographic characteristics and binary logistic regression to assess the association between dementia and sociodemographic factors. Results: We observed that the prevalence of dementia in Latin America is 15.6%, varying depending on the country (Argentine = 7.83 and Bolivia = 28.5%). The variables most associated with dementia were race and age. It does not seem to be associated with the pandemic but with social and socio-health factors. Conclusion: The prevalence of dementia shows a significant increase in Latin America, attributable to a constellation of ethnic, demographic, and socioeconomic factors.